2019
DOI: 10.1080/14737167.2019.1628641
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and costs of patients prior to colorectal surgery

Abstract: Objective: To assess the quality of life and societal costs of patients prior to colorectal surgery in the Netherlands. Methods: This study is embedded in a previous randomized controlled trial (SANICS II). The quality of life was measured using EQ-5D-5L questionnaires. The iMTA medical consumption questionnaire (iMCQ) and the iMTA productivity costs questionnaire (iPCQ) were used to identify and measure healthcare and productivity costs. Subgroup analyses were performed based on age and gender. Results: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The societal costs for CRC survivors are lower compared to the average annual health expenses of the general Dutch population in 2017 (€5100), but are higher compared to the average annual health expenses of individuals with cancer in 2017 (€343) or individuals with CRC (€35) [ 48 , 49 ]. Additionally, CRC survivors 2–10 years post-diagnosis showed slightly lower utility scores compared to the general Dutch population (0.87) [ 37 ], lower utility scores than patients prior to CRC surgery in the Netherlands (0.88) [ 50 ], and higher utility scores compared to CRC patients in the primary treatment phase [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The societal costs for CRC survivors are lower compared to the average annual health expenses of the general Dutch population in 2017 (€5100), but are higher compared to the average annual health expenses of individuals with cancer in 2017 (€343) or individuals with CRC (€35) [ 48 , 49 ]. Additionally, CRC survivors 2–10 years post-diagnosis showed slightly lower utility scores compared to the general Dutch population (0.87) [ 37 ], lower utility scores than patients prior to CRC surgery in the Netherlands (0.88) [ 50 ], and higher utility scores compared to CRC patients in the primary treatment phase [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highly variable costs are in accordance with previous studies, where the majority of cancer survivors had little or no costs and a small number incurred very high costs [ 51 ]. The mean costs in this population were hypothesized to be lower than costs in the primary treatment phase, which several studies have demonstrated to be associated with highest costs [ 50 , 52 ]. Interestingly, the mean costs of this study were only slightly lower than the costs of rehabilitation (€2106, 6–18 months from diagnosis) and remission (€2812, > 18 months from diagnosis) phase as demonstrated by Färkkilä et al [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, in one study, healthcare utilisation per patient was estimated using the iMCQ at 0.88 ± 0.15. [24] Under the assumption of a small or medium effect of our eHealth strategy (d = 0.35), an α of 0.05 and a power of 0.80, a total sample size of 260 patients is required. The total study population is set at 280 patients (140 patients per arm) to account for loss to follow-up and nonadherence to the intervention.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Theoretically, a non-invasive intervention with an estimated low complication rate could potentially result in a favorable QoL as a result of better tolerance. The effects on QoL in patients with metastatic stage IV colorectal cancer has been evaluated in studies of various designs, and in different settings (12)(13)(14). Well established questionnaires give the opportunity to include many patients and reach reliable and validated results in a practical manner.…”
mentioning
confidence: 99%